Trade and Cities - Karayalcin, Cem; Yilmazkuday, Hakan (World Bank, Washington, DC, 2014)
Many developing countries display remarkably high degrees of urban concentration that are incommensurate with their levels of urbanization. The cost of excessively high levels of urban concentration can be very high in terms of overpopulation, congestion, and productivity growth. One strand of the theoretical literature suggests that such high levels of concentration may be the result of restrictive trade policies that trigger forces of agglomeration. Another strand of the literature, however, points out that trade liberalization itself may exacerbate urban concentration by favoring the further growth of those large urban centers that have better access to international markets. The empirical basis for judging this question has been weak so far; in the existing literature, trade policies are poorly measured (or are not measured, as when trade volumes are used spuriously). Here, new disaggregated tariff measures are used to empirically test the hypothesis. A treatment-and-control analysis of pre- versus post-liberalization performance of the cities is also employed in liberalizing and non-liberalizing countries. It is found that (controlling for the largest cities that have ports and, thus, have better access to external markets) liberalizing trade leads to a reduction in urban concentration.